Labor Reallocation and Demographics - Joanna Tyrowicz; Lucas Van der Velde (Institute of Labor Economics (IZA), 2017)
We explore data from all transition economies over nearly two decades, providing insights on the mechanisms behind labor force reallocation. We show that worker flows between jobs in different industries are rare relative to the demographic flows of youth entry and elderly exit. The same applies to the flows between state-owned enterprises and private firms. In fact, evidence suggest that changes in the demand for labor were accommodated mostly through demographic flows, with a smaller role left for job transitions. We also show that the speed of changing the ownership structure in the economy has driven exits to retirement, in particular the early exits.
Keywords: P2; P5; D2; J6; 330; hirings; separations; transition; worker flows; unemployment; retirement